Miners Federation of Great Britain statement on owners proposal, 27 April 1926 (page 4)
1926-04-27 "Miners Federation of Great Britain statement on owners proposal, 27 April 1926 (page 4)" [g0439004.jpg], 27 April 1926, Miners' Federation of Great Britain